Sharenting – modern parenting and the position of children in the digital space - Čižmešija, Marija; Dmitrovski, Ivanka (Rethinking childhood II: child and space, 2026)
The trend of parents publishing photos of children and minors (sharenting) has increased. Often, parents create their child’s digital identity without the child’s knowledge or consent, ignoring their right to privacy and potential negative future consequences. By sharing private life content, parents expose their children to public comments that may have adverse effects in the future. This paper presents the results of a small study involving parents from a kindergarten in Zagreb County (N=97). The aim of the research was to examine the habits and activities of children in the digital environment, but also parents’ habits, activities and level of digital literacy, as well as their knowledge and attitudes about the consequences of sharing. The research also aimed to raise awareness among participating parents about the importance of responsible behaviour and protecting their child’s identity in a potentially dangerous digital environment.